Potential Probiotic Pediococcus pentosaceus M41 Modulates Its Proteome Differentially for Tolerances Against Heat, Cold, Acid, and Bile Stresses - Baig, Mohd Affan (Frontiers Media S.A., 2022)
10.3389/fmicb.2021.731410